Two Dimensional Finite Difference Time Domain Tool for Cancer Detection on Scilab - Pal, Shelendra; Rajkumar, Rajkumar; Sharma, Vipul (International Journal of Computer Sciences and Engineering, 2025)
Cancer is the world’s most proliferating and dangerous disease. Due to lack of proper knowledge of cancer, it is spreading among the people and a large number of people are dying from cancers such as lung, blood, breast, palm, liver, stomach, colorectal, prostate, bladder, pancreatic cancer etc. There were an estimated 14.1 million cancer cases around the world in 2012 and out of these 7.4 million and 6.7 million cases were in men and women respectively [21,22,23]. Cancer cells continue to increase new abnormal cells, many cellular changes have been reported to be associated with malignant process till date. For cancer detection a versatile method such as finite difference time domain is very frequently used in this era. In this paper we propose a two-dimensional finite difference time domain (FDTD) numerical simulation technique using Scilab, for early detection of cancer tissue, early phase can provide more treatment options, less invasive surgery and increases the survival rate